Bioactive immunostimulants as health-promoting feed additives in aquaculture: A review. Issue 130 (November 2022) - Vijayaram, Seerengaraj; Sun, Yun-Zhang; Zuorro, Antonio; Ghafarifarsani, Hamed; Van Doan, Hien; Hoseinifar, Seyed Hossein
Abstract: Bioactive immunostimulants could be derived from different sources like plants, animals, microbes, algae, yeast, etc. Bioactive immunostimulants are the most significant role to enhance aquatic production, as well as the cost of this method, which is effective, non-toxic, and environment-friendly. These immunostimulants are supportive to increase the immune system, growth, antioxidant, anti-inflammatory, and disease resistance of aquatic animals' health and also improve aquatic animal feed. Diseases are mainly targeted to the immune system of aquatic organisms in such a way that different processes of bioactive immunostimulants progress are considered imperative techniques for the development of aquaculture production. Communicable infections are the main problem for aquaculture, while the mortality and morbidity connected with some outbreaks significantly limit the productivity of some sectors. Aquaculture is considered the mainly developing food production sector globally. Protein insists is an important issue in human nutrition. Aquaculture has been an exercise for thousands of years, and it has now surpassed capture fisheries as the most vital source of seafood in the world. Limited study reports are available to focal point on bioactive immunostimulants in aquaculture applications. This review report provides information on the nutritional administration of bioactive immunostimulants, their types, functions, and beneficial impacts on aquatic animals' health as well as for the feed quality development in the aquaculture industry. The scope of this review combined to afford various kinds of natural derived bioactive molecules utilization and their beneficial effects in aquaculture applications. Graphical abstract: Image 1 Highlights: Biomolecules are most important role in aquaculture production. Different kinds of biomolecules are identified in plants, animals and microbes and also utilized to enhance healthy aquatic productions. Biomolecules are having numerous beneficial activities like enhance immune system, disease resistance, growth and gut microbiota modulation. Biomolecules utilized to enhance feed quality and aquatic productions as well as biomolecules are alternative development of modern aquaculture industry. Biomolecules are non toxic effects and cost effective methods.